2023
DOI: 10.3390/nu15030724
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Impacts on Changes in Diversity and Abundance of the Murine Microbiome during Progression and Treatment of Cancer

Abstract: The intestinal microbial population is recognized for its impact on cancer treatment outcomes. Little research has reported microbiome changes during cancer progression or the interplay of disease progression, dietary sugar/fat intake, and the microbiome through surgery and chemotherapy. In this study, the murine gut microbiome was used as a model system, and changes in microbiome diversity, richness, and evenness over the progression of the cancer and treatment were analyzed. Mice were categorized into four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Concurrently, several studies have demonstrated a connection between artificial sweetener intake and weight gain, a relationship our research corroborates (53, 54). Yet, a more exhaustive examination is imperative to fully understand BMI's mediating role, and the mechanism might be involved in tied to modifications in gut microbiota, the release of gut hormones, and metabolic aggregation (55,56). For instance, research has shown that dietary patterns, including ASB, can impact the composition of gut microbiota, leading to the transformation of carcinogenic substances such as bile acids into metabolites like secondary bile acids and hydrogen sulfide, ultimately promoting the development of CRC (57).…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, several studies have demonstrated a connection between artificial sweetener intake and weight gain, a relationship our research corroborates (53, 54). Yet, a more exhaustive examination is imperative to fully understand BMI's mediating role, and the mechanism might be involved in tied to modifications in gut microbiota, the release of gut hormones, and metabolic aggregation (55,56). For instance, research has shown that dietary patterns, including ASB, can impact the composition of gut microbiota, leading to the transformation of carcinogenic substances such as bile acids into metabolites like secondary bile acids and hydrogen sulfide, ultimately promoting the development of CRC (57).…”
Section: Discussionmentioning
confidence: 99%
“… 301 The presence of Akkermansia , a mucin-degrading bacterium, is strongly associated with favorable outcomes in cancer patients. 302 Moreover, inulin, a polysaccharide dietary fiber, can enhance the effectiveness of anti-PD-1 therapy by increasing the abundance of beneficial commensal microbiota genera (e.g., Akkermansia , Lactobacillus and Roseburia ) and SCFAs, further increasing the number of stem-like T-cell factor-1 (Tcf1) + PD-1 + CD8 + T cells. 303 Similarly, oral administration of pectin, another dietary polysaccharide fiber, can largely improve the efficacy of anti-PD-1 mAbs by increasing the number of butyrate-producing bacteria, which is sufficient to promote T-cell infiltration and activation in the TME.…”
Section: Diet Changes the Gut Microbiome In Conjunction With Antitumo...mentioning
confidence: 99%